Geochemical Analyses and Provenance Determination of White Marble Samples from Churches in North Jordan - Bashaireh, Khaled al- (Bulletin of ASOR, 2015)
Physical, mineralogical, and chemical characteristics of white marble collected from architectural elements of churches located in northern Jordan are used to determine their provenance and shed light on the regions marble trade during the late classical period. The samples were examined macroscopically and were subjected to a series of analytical techniques, including optical microscopy, X-ray diffraction, and mass spectrometry. In addition, a subset of samples was examined using cathodoluminescence microscopy and electron paramagnetic resonance spectroscopy. The data obtained were compared with the main reference databases of known Mediterranean marble quarries exploited in antiquity. Proconnesos-1 in Marmara, Turkey, is the most probable major source of the medium-grained samples, and Docimium, Turkey, and Carrara, Italy, are the most probable sources of the two fine-grained marbles. The coarse-grained sample is most probably from Naxos, Greece, while the anomalous sample is probably from Proconnesos-1 or Paros 2 (3), Greece. Although some of the samples might have been from reused architectural elements, their source did not differ from the rest of the samples, indicating that the white Proconnesos marble was the main source for the marble trade during Roman and Byzantine periods.